Gaál-Szabó, Péter. “Ah done been tuh de horizon and back”: Zora Neale Hurston’s Cultural Spaces in Their Eyes Were Watching God and Jonah’s Gourd Vine. Debrecener Studien zur Literatur 16. Frankfurt am Main: Peter Lang, 2011. 134 pages. - Bailey, Ted (FOCUS: Papers in English Literary and Cultural Studies, 2014)
Written originally as a PhD dissertation, ‘Ah done been tuh de horizon and back’: Zora Neale Hurston’s Cultural Spaces in Their Eyes Were Watching God and Jonah’s Gourd Vine examines spatial paradigms in Hurston’s two best-known works and how Hurston uses cultural space to establish female subjectivity, engaging along the way concepts and language that many undergraduates would find difficult to digest. For the academic reader, however, the book presents an intriguing study of how theory can be used to view an old text through a new prism.